Differential effect of zoledronic acid on normal trabecular and cortical bone density in oncologic patients with bone metastases - Quattrocchi, Carlo C. (J Bone Oncol, 2012)
PURPOSE: To evaluate bone density changes at the level of normal bone and bone metastases after zoledronic acid (ZA) treatment in oncologic patients. MATERIALS AND METHODS: We retrospectively evaluated 72 consecutive adult patients with histologically confirmed solid tumors with at least 1 newly diagnosed bone metastatic lesion. Bone metastases were diagnosed by bone scans and confirmed with computed tomography (CT). Patients received intravenous ZA, 4 mg, by 15-min infusion every 28 day through a peripheral or a central venous access and were monitored for at least 3 months and a maximum of 24 months. Bone density was determined at the level of bone metastases and at the level of normal trabecular and cortical bone using a ROI-based approach. RESULTS: A significant increase was demonstrated at the level of normal trabecular bone of the calvarium and the femoral neck. No significant increase of density was observed at the level of the normal cortical bone. Bone metastases showed a significant increase in CT density as compared to baseline up to 24 months after zoledronic acid. CONCLUSION: We have found that long term treatment with ZA increases trabecular bone density in oncologic patients whereas normal cortical bone changes are not detectable.